Synthesis of Ag2O Nanoparticles via Fresh Pomegranate Peel Extract for Bioapplications - Wedian K. Abad; Ahmed N. Abd; Nadir Fadhil Habubi (Nano Biomedicine and Engineering, 2023)
Fresh pomegranate peel extract was employed to synthesize silver oxide nanoparticles (Ag2O NPs). Rapid formation of stable Ag2O NPs was observed on exposure to the aqueous fresh pomegranate peel extract with solution of AgNO3. The Ag2O NPs were characterized by X-ray analysis, scanning electron microscopy (SEM), ultraviolet–visible (UV–Vis) spectroscopy, and Fourier transform infrared spectroscopy (FTIR). The X-ray diffraction (XRD) confirmed that the forming Ag2O NP has a crystalline size of 37 nm, while SEM micrographs revealed a comparatively spherical shape, with the size of ~ 64 nm. The Ag2O spectrum displayed a peak in the visible range and a blue shift at 461 nm corresponding to the Plasmon absorbance of silver nanoparticles. Four bacterial strains and one type of fungus were tested using Ag2O NPs. The results showed the negative influence of Ag2O NPs on the growth rate, thus implying the significance of the present study in production of biomedical products.